5G wireless technologies. - Alexiou, Angeliki (The Institution of Engineering and Technology, 2017)
Mobile data traffic is expected to exceed traffic from wired devices in the next couple of years. This emerging future will be empowered by revolutionary 5G radio network technologies with a focus on application-driven connectivity, transparently deployed over various technologies, infrastructures, users and devices to realise the vision of 'the Internet of Everything'. This book presents a roadmap of 5G, from advanced radio technologies to innovative resource management approaches and novel network architectures and system concepts. Topics covered include challenges for efficient multi-service coexistence for 5G below 6GHz; new quasi-deterministic approaches to channel modelling in millimetre-wave bands; large scale antenna systems; effects of densification and randomness of infrastructure deployment in cellular networks; wireless device-to-device (D2D) Links for machine-to-machine (M2M) communication; caching in large wireless networks; full duplexing; decoupled uplink and downlink access in heterogeneous networks; wireless networks virtualisation; and regulation, business and technology perspectives on licensed shared access (LSA) and three-tier spectrum sharing models. 5G Wireless Technologies is an essential guide to this emerging system for researchers, engineers and advanced students working in telecommunications and networking.
Keywords: Wireless communication systems -- Technological innovations.; elektronické knihy; electronic books